Inflammatory Amplification: A Central Tenet of Uterine Transition for Labor - Leimert, Kelycia B.; Xu, Wendy; Princ, Magdalena M.; Chemtob, Sylvain; Olson, David M. (Frontiers in Cellular and Infection Microbiology, 2021)
In preparation for delivery, the uterus transitions from actively maintaining quiescence during pregnancy to an active parturient state. This transition occurs as a result of the accumulation of pro-inflammatory signals which are amplified by positive feedback interactions involving paracrine and autocrine signaling at the level of each intrauterine cell and tissue. The amplification events occur in parallel until they reach a certain threshold, ‘tipping the scale’ and contributing to processes of uterine activation and functional progesterone withdrawal. The described signaling interactions all occur upstream from the presentation of clinical labor symptoms. In this review, we will: 1) describe the different physiological processes involved in uterine transition for each intrauterine tissue; 2) compare and contrast the current models of labor initiation; 3) introduce innovative models for measuring paracrine inflammatory interactions; and 4) discuss the therapeutic value in identifying and targeting key players in this crucial event for preterm birth.